2021
DOI: 10.1186/s42523-021-00146-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical health issues, reproductive hormones, and metabolic hormones associated with gut microbiome structure in African and Asian elephants

Abstract: Background The gut microbiome is important to immune health, metabolism, and hormone regulation. Understanding host–microbiome relationships in captive animals may lead to mediating long term health issues common in captive animals. For instance, zoo managed African elephants (Loxodonta africana) and Asian elephants (Elephas maximus) experience low reproductive rates, high body condition, and gastrointestinal (GI) issues. We leveraged an extensive collection of fecal samples and health records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 125 publications
5
23
0
Order By: Relevance
“…Four bacterial phyla are core members of the mammalian gut microbiome including Bacteroidetes, Firmicutes, Proteobacteria and Actinobacteria ( 51 ). Consistent with previous research findings ( 5 , 12 , 52 , 53 ), our results showed the gut microbiome of captive African and Asian elephants was dominated by two phyla: Bacteroidetes and Firmicutes , following by Spirochaetes, Verrucomicrobia and Protrobacteria ( Figures 2A , B ). Compared to dominant phyla in other animals like cow ( Clostridiales and Prevotellaceae ) or termite ( Spirochetes and Fibrobacteres ), the dominant phyla in elephants allow them digest various plant biopolymers ( 9 , 54 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Four bacterial phyla are core members of the mammalian gut microbiome including Bacteroidetes, Firmicutes, Proteobacteria and Actinobacteria ( 51 ). Consistent with previous research findings ( 5 , 12 , 52 , 53 ), our results showed the gut microbiome of captive African and Asian elephants was dominated by two phyla: Bacteroidetes and Firmicutes , following by Spirochaetes, Verrucomicrobia and Protrobacteria ( Figures 2A , B ). Compared to dominant phyla in other animals like cow ( Clostridiales and Prevotellaceae ) or termite ( Spirochetes and Fibrobacteres ), the dominant phyla in elephants allow them digest various plant biopolymers ( 9 , 54 ).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, African and Asian elephants had different gene abundance patterns. This also has been shown previously by Keady et al ( 12 ) that African and Asian elephants have different microbial structure and dissimilar bacterial composition ( 12 ). The difference was mainly caused by the host species as the PERMANOVA analysis showed that the host species explained 63% of the variation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, Actinobacteria represent only a very minor fraction of the mammalian gut, in particular when compared to soil samples; still, antibiotic-producing Actinobacteria have been isolated from the faeces of a variety of mammals [39][40][41] . Studies analysing the microbiome composition of elephants, the closest living relative to mammoths, report the presence of actinobacterial reads in low abundance, including Streptomyces, Sanguibacter, Micromonospora and Saccharopolyspora, but not Oerskovia [42][43][44] . Species of Streptomyces and Micromonospora have been isolated from the faeces of elephants 41,45 .…”
Section: Discussionmentioning
confidence: 99%
“…We conducted 16 S rRNA gene amplicon library preparation of the V4−V5 region as specified in Keady et al (2021) and sequenced the final 4 nM library on an Illumina MiSeq with a 2 × 300 bp v3 kit.…”
Section: Methodsmentioning
confidence: 99%